Blue Light Therapy Glasses in Parkinson’s Disease: Patients’ Experience - Katarzyna Smilowska; Daniel J. van Wamelen; Antonius M. C. Schoutens; Marjan J. Meinders; Bastiaan R. Bloem (Parkinson's Disease)
Background. Blue light glasses have been introduced as a possible new treatment option to treat sleep disturbances in patients with Parkinson disease (PD). Assessing patient attitudes represents a key step in the road towards formal testing and introduction into clinical practice. Specifically, we aimed to assess how patients experience the use of blue light glasses, aiming to optimise compliance in upcoming clinical trials where these glasses will be tested for efficacy. Methods. We invited 58 PD patients who had used the blue light glasses for at least one week on a daily basis to complete an online survey about their experiences and self-reported impact. For this purpose, the System Usability Scale was used, supplemented with additional questions about (side)effects. A total of 31 patients (53%) replied. Results. 74% of respondents reported subjective improvements in night-time sleep, daytime sleepiness, depressive symptoms, motor functioning, or a combination thereof. The median score for the System Usability Scale (SUS; 0–100 range, higher scores indicating better performance) was 70.0. A total of 26 patients (84%) had an overall positive attitude towards the technique, with patients rating the glasses with an average score of 6.9 ± 2.0 (SD) out of 10. Except for one patient, all responders would like to continue using the glasses, mostly because they considered it a useful aid. Conclusion. Blue light therapy appears to have a positive effect on sleep, mood, and motor symptoms in PD. PD patients had an overall positive attitude towards blue light glasses as treatment for sleep disorders.